HUKUM ISLAM DAN PENGGUNAAN TEKNOLOGI INFORMASI DI INDONESIA - Azhar, Azhar (Proceeding International Seminar of Islamic Studies, 2024)
The relationship between Islamic law and the use of information technology, such as the world's 5th largest smartphone user, while Indonesia is ranked 4th in the world for Facebook users. Of the 80% of internet users, especially in Indonesia, are teenagers aged 15-19 years, namely almost 18.4%, this shows that information openness in society is caused by the development of sophistication in information technology. Everything that happens in other parts of the world can happen within seconds of being known by humans in other parts of the world. Technology was created to serve and make it easier for humans to carry out their life activities. In Islamic teachings we find Allah's affirmation through QS al-Hujurāt/49 verse 12 regarding facing advances in information technology. Information technology cannot be separated from the development of Islamic law because of laws and developing legal information for the wider community.